SOCIAL DETERMINANTS FACTORS RELATED TO TUBERCULOSIS IN PADANG CITY - Sejati Sejati; Awaluddin Awaluddin; Rahmi Hidayanti (HUMAN CARE JOURNAL, 2020)
Pulmonary tuberculosis is an infectious disease and is still a global challenge, the number of sufferers continues to increase until now there is no country that is free of tuberculosis. The number of Tuberculosis cases in Padang City in 2018 was 566,623 cases increased compared to 2017 which was 446,732 cases. This study aims to analyze the factors associated with the incidence of tuberculosis in the work area of Pamancungan Public Health Center, Padang Selatan District based on gender, economic status, education level and age. This type of research is case control. Respondents in this study were patient with positive Acid Fast Bacili, there were 70 respondents with 1: 1 case and control ratio. The results of the study with the chi square test showed that the gender p value 0.016; OR 3333 (95% CI 1,235 - 8,997), economic status p value 0,000; OR 7,667 (95% CI 2,595 - 22,646), education p value of 0.010; OR 4,070 (95% CI 1,352–12,255) had a significant relationship with the incidence of Tuberculosis (p <0.005), while the age value of p was 0.632; OR 0.795 (95% CI0.311 - 2.034) had no relationship with the incidence of Tuberculosis p value of 0.632 (p> 0.05)